Experimental determination of the effective point of measurement in electron beams using a commercial scintillation detector. (December 2017) - Simiele, E.A.; Smith, B.R.; Culberson, W.S.
Abstract: Purpose: A commercial plastic scintillation detector was used to determine the effective point of measurement (EPOM) of three cylindrical ionization chambers in four clinical electron beams. The experimentally determined EPOM values were compared to Monte Carlo (MC)-calculated EPOM values from the literature. The energy dependence of the EPOM was also investigated. Methods: Percent depth dose (PDD) curves were measured with an Exradin W1 scintillation detector and were used as a representative PDD to water. Depth dose curve measurements were also acquired with the Exradin A18, A1SL, and A28 cylindrical ionization chambers. To obtain a depth dose to an equivalent chamber volume made of water (DDCVW), the raw ionization chamber depth dose data were corrected by the chamber fluence correction factor and restricted mass collisional stopping power ratio at each measurement depth. A non-linear least squares fitting technique was utilized to determine the EPOM for the three chambers. The W1 PDD curve was shifted by small increments, Δz, until the ratio of the W1 PDD to the ionization chamber DDCVW was depth independent. The optimal shift was used as an estimate of the EPOM for each chamber. Results: The ratios of the unshifted W1 PDD to the chamber DDCVW decreased with depth. After shifting by the optimal Δz value, the ratios of the W1 PDD to the chamber DDCVW were constant with depth with an average value near unity, which implies that the two profiles are in good agreement with each other. The calculated EPOM shifts and associated uncertainties (expressed as a fraction of the chamber cavity radius, r cav ) for the A18, A1SL, and A28 ionization chambers were 0.21 ± 0.04, 0.10 ± 0.05, and 0.22 ± 0.03, respectively. Conclusions: The EPOM shifts determined in this work agree with calculations by other investigators to within one standard deviation for the A18 and A1SL ionization chambers. This agreement confirms that the AAPM TG51-recommended EPOM shift of 0.5 × r cav is not accurate for the A18 and A1SL chambers for electron beam dosimetry. Contrary to previous works, there was no observable trend in the measured EPOM values with electron energy for each chamber. Highlights: The effective point of measurement of three cylindrical ion chambers was experimentally determined. The measured effective point of measurement shifts for the ion chambers agreed with Monte Carlo values from literature. Shifts were independent of electron energy indicating that a single shift can be used over the energy range investigated.